Wanderlust : a history of walking - Solnit, Rebecca (Verso, 2002)
What does it mean to be out walking in the world, whether in a landscape or a metropolis, on a pilgrimage or a protest march? In this first general history of walking, Rebecca Solnit draws together many histories to create a range of possibilities for this most basic act. Arguing that walking as history means walking for pleasure and for political, aesthetic, and social meaning, Solnit homes in on the walkers whose everyday and extreme acts have shaped our culture, from the peripatetic philosophers of ancient Greece to the poets of the Romantic Age, from the perambulations of the Surrealists to the ascents of mountaineers. With profiles of some of the most significant walkers in history and fiction - from Wordsworth to Gary Snyder, from Rousseau to Argentina's Mother of the Plaza de Mayo, from Jane Austen's Elizabeth Bennet to Andre Breton's Nadja - "Wanderlust" offers a provocative and profound examination of the interplay between the body, the imagination, and the world around the walker.